Chemical Properties and Biological Activities of Cyclopentenediones: A Review - Sevcikova, Zuzana; Pour, Milan; Novak, David; Ulrichova, Jitka; Vacek, Jan (Mini Reviews in Medicinal Chemistry, 2014)
Cyclopentenediones (CPDs) are secondary metabolites of higher plants, fungi, algae, cyanobacteria and bacteria. A common denominator of CPDs is the cyclopent-4-ene-1,3-dione skeleton (1), which is modified by several functional groups. The heterogeneity of these substitutions is reflected in around one hundred CPDs reported to date. Most of the derivatives were isolated primarily from plant sources. Synthetic analogues were then prepared with new biological activities and more interesting pharmacological potential. Antifungal substances called coruscanones (2, 3) are the most studied of the CPDs. Other intensely investigated CPDs include lucidone (4), linderone (5), asterredione (6), involutone (7), nostotrebin 6 (8), TX-1123 (9), G2201-C (10), madindolines (11, 12) and many others. In addition to antibacterial and antifungal effects, a broad spectrum of biological activities for CPDs has been reported in the past two decades, especially anti-inflammatory, cytostatic and specific enzyme inhibitory activities. The CPD skeleton has been identified in a number of substances isolated from the plant kingdom; hence, CPDs can be referred to as a new group of natural bioactive substances. The main goal of this review is to define CPDs with respect to basic chemistry, isolation, synthetic approaches and description of their biological effects. Special attention is given to a detailed view into biological activities of CPDs in vitro and their phamacological potential.
Keywords: cyclopentenediones